2023
DOI: 10.1186/s12951-023-02026-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of metastatic sentinel lymph nodes by dual-targeting melittin nanoparticles

Yanfeng Dai,
Xiang Yu,
Yuehong Leng
et al.

Abstract: Sentinel lymph node (SLN) metastasis is an important promoter of distant metastasis in breast cancer. Therefore, the timely diagnosis and precise treatment are crucial for patient staging and prognosis. However, the simultaneous diagnosis of metastasis and the implementation of imaging-guided SLN therapy is challenging. Here, we report a melittin-loaded and hyaluronic acid (HA)-conjugated high-density lipoprotein (HDL) mimic phospholipid scaffold nanoparticle (MLT-HA-HPPS), which dually-target to both breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, Mel-HA-Lip performed more obvious antitumor effects compared with Mel-Lip ( 170 ). Dai and colleagues developed dual-targeting nanoparticles carrying melittin with HA-conjugated high-density lipoprotein (HDL) as the phospholipid scaffold (MLT-HA-HPPS) to target breast cancer and its sentinel lymph node (SLN) ( 88 ). MLT-HA-HPPS exhibited effective cytotoxicity on mouse mammary adenocarcinoma 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mel-HA-Lip performed more obvious antitumor effects compared with Mel-Lip ( 170 ). Dai and colleagues developed dual-targeting nanoparticles carrying melittin with HA-conjugated high-density lipoprotein (HDL) as the phospholipid scaffold (MLT-HA-HPPS) to target breast cancer and its sentinel lymph node (SLN) ( 88 ). MLT-HA-HPPS exhibited effective cytotoxicity on mouse mammary adenocarcinoma 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tumoricidal properties of melittin on breast cancer cells have been investigated ( 86 , 87 ). Melittin could impede primary tumor growth and inhibit the growth of the metastatic sentinel lymph node in breast cancer models in vitro and in vivo ( 88 ). Melittin directly acts on MCF7 breast cancer cells ( 81 , 89 ) and suppresses the migration of breast cancer cell, MDA-MB-231 cell line ( 90 ).…”
Section: Antitumor Potential Of Melittinmentioning
confidence: 99%
“…For example, hyaluronic acid (HA) not only increases the accumulation of NPs in the CD44-expressed tumor region but also results in the release of therapeutic agents in the TME by hyaluronidase-mediated degradation of HA [ 121 ]. Therefore, the insertion of HA moieties as an effective targeting element within NP formulations is a promising strategy for tumor treatment [ 122 , 123 ]. Jia et al found that chlorin e6 (Ce6) could form a stable nanocomplex with MLT and effectively shield the hemolytic activity of MLT [ 124 ].…”
Section: Targeted Delivery Strategies Of Mlt For Tumor Therapymentioning
confidence: 99%